Level of Satisfaction with Activities Sharing Session - Sendhitasari, Aulia Ferina; Lidanta, Fairuz Zahirah; Salsabila, Syifa Aria; Sadewa, Rizki; Fakhrurroja, Hanif (Yayasan Asmin Intelektual Berkah, 2024)
Human resource strategy development (people development) is a critical aspect in the growth and success of an organization, especially in the field of IT consulting to foster talent, encourage innovation, and improve overall organizational performance. Sharing session, as a form of interactive learning, offers a platform for employees to exchange ideas, best practices, and lessons learned, facilitating the development of a knowledgeable and adaptable workforce. Sharing sessions helping companies create an environment where knowledge can be shared, accessed, and used effectively by all members of the organization is the goal of knowledge management itself. This research was conducted using qualitative methods through a survey of employees, especially for the IT consulting industry to see the effect of sharing sessions in decision making which is then validated through a survey of top management to see satisfaction with the accuracy of employees in making decisions